INTEGRASI AGAMA DAN SAINS PADA MATA PELAJARAN PENDIDIKAN KEWARGANEGARAAN (PKN) DI SD NEGERI 200508 SIHITANG - Yukhairiza Simatupang, Ananda (Tarbiyah : Jurnal Pendidikan Agama Islam, 2025)
This study aims to analyze the integration of religion and science in the Civics Education (PKN) subject at SD Negeri 200508 Sihitang. The primary focus of this research is how to connect religious values with scientific concepts in PKN lessons, and how these are implemented in the classroom by teachers. The identified problem is the lack of understanding about the importance of combining religious teachings, scientific knowledge, and citizenship in the learning process. The research employs a qualitative descriptive approach, with data collection through observation, interviews, and document studies at the school. The purpose of this study is to explore the extent to which the integration of religion and science is applied in PKN lessons and to provide recommendations for the development of a more holistic curriculum and teaching strategies. The findings show that the integration of religion and science in PKN lessons at SD Negeri 200508 Sihitang is still limited and not fully optimized. While teachers make efforts to align religious values with citizenship concepts, this integration is mostly focused on character and moral development. In conclusion, further development is needed to systematically and structurally integrate religion and science in PKN material, enabling students to gain a deeper and more comprehensive understanding of citizenship from both a spiritual and scientific perspective.